2016
DOI: 10.1089/jpm.2015.0326
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Advance Directive Possession: Role of Demographic Factors, Religious Affiliation, and Personal Health Values in a National Survey of Older Adults

Abstract: Background: Black and Hispanic older Americans are less likely than white older Americans to possess advance directives. Understanding the reasons for this racial and ethnic difference is necessary to identify targets for future interventions to improve advance care planning in these populations. Methods: The aim of the study was to evaluate whether racial and ethnic differences in advance directive possession are explained by other demographic factors, religious characteristics, and personal health values. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
99
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 27 publications
14
99
1
1
Order By: Relevance
“…Consistent with previous research, our data revealed strong associations between advance directive completion and racial/ethnic background, education, and marital status [15,16]. Being married or widowed was associated with advance directive possession, with widowed participants having the highest completion rate.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with previous research, our data revealed strong associations between advance directive completion and racial/ethnic background, education, and marital status [15,16]. Being married or widowed was associated with advance directive possession, with widowed participants having the highest completion rate.…”
Section: Discussionsupporting
confidence: 90%
“…Significant attention has been paid to demographic and socioeconomic factors that may explain non-completion. With few exceptions, studies have reported lower completion rates among black, Hispanic and other non-white groups [15][16][17]. These same studies also found that lower education and socioeconomic status were associated with lower completion rates.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Study results demonstrate access to a structured pACP program in hospital-based clinics was successful in engaging an underserved cohort of largely young, poor, non-college educated, African-American and Latino/Hispanic adolescents and their families, thereby overcoming barriers to EOL research in this group (Grady, 2005; Huang, Neuhaus, & Chiong, 2016; Johnstone & Kanitsaki, 2009) and health disparities in ACP (AARP, 2003; Arenella, 2016; Boucher, Raghavan, Smith, Arnold, & Johnson, 2016). Training facilitators to certification and providing structure overcame other barriers, including clinicians not knowing the right thing to say, concerns about parents having unrealistic expectations, and lack of parental readiness (Davies et al, 2008; Durall, Zurakowski, & Wolfe, 2012; Sudore & Fried, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Further exploration of the relationships between older adults’ perceptions related to their EOL planning and their religious and ethnic backgrounds could better promote patient‐centered care. For example, Huang, Neuhaus, and Chiong found that among American adults aged 50 years and older, black race was an independent predictor for completing an EOL plan after adjusting for other demographic variables such as age, gender, religious affiliations, and self‐care behaviors. Barriers and facilitators to EOL planning for older adults and health care providers (eg, communicating about sensitive topics related to EOL planning in such as home, outpatient, and palliative care settings) could be further explored …”
Section: Discussionmentioning
confidence: 99%